The Melatonin Type 2 Receptor Agonist IIK7 Attenuates and Reverses Morphine Tolerance in Neuropathic Pain Rats Through the Suppression of Neuroinflammation in the Spinal Cord - Yaswanth Kuthati; Chih-Shung Wong (Pharmaceuticals)
Background: Morphine analgesic tolerance (MAT) limits the clinical application of morphine in the management of chronic pain. IIK7 is a melatonin type 2 (MT2) receptor agonist known to have antioxidant properties. Oxidative stress is recognized as a critical factor in MAT. This study sought to assess the impact of IIK7 on the progression of MAT and its potential to reverse pre-existing MAT. Methods: Wistar rats underwent partial sciatic nerve transection (PSNT) surgery to induce neuropathic pain (NP). Seven days post nerve transection, we implanted an intrathecal (i.t.) catheter and linked it to an osmotic pump. Rats were randomly divided into the following groups: sham-operated/vehicle, PSNT/vehicle, PSNT/IIK7 50 ng/h, PSNT/MOR 15 g/h, and PSNT/MOR 15 g + IIK7 50 ng/h. We implanted two i.t. catheters for drug administration and the evaluation of the efficacy of IIK7 in reversing pre-established MAT. We linked one to an osmotic pump for MOR or saline continuous i.t. infusion. On the 7th day, the osmotic pump was disconnected, and 50 μg of IIK7 or the vehicle was administered through the second catheter. After 3 h, 15 μg of MOR or saline was administered, and the animal behavior tests were performed. We measured the levels of mRNA for Nrf2 and HO-1, pro-inflammatory cytokines (PICs), and the microglial and astrocyte activation in the spinal cord. Results: The co-administration of IIK7 with MOR delayed MAT development in PSNT rats by restoring Nrf2 and HO-1 while also inhibiting the microglial-cell and astrocyte activation, alongside the suppression of PICs. Additionally, a single injection of high-dose 50 μg IIK7 was efficient in restoring MOR’s antinociception in MOR-tolerant rats. Conclusions: Our results indicate that the co-infusion of ultra-low-dose IIK7 can delay MAT development and a high dose can reverse pre-existing MAT.